1991
DOI: 10.2337/diacare.14.11.1001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Hypoglycemic Coma in Children With IDDM

Abstract: In this group of children, improvement of glycemic control apparently led to an increase in the incidence of severe hypoglycemia. In children with recurrent hypoglycemic coma and undetectable C-peptide levels, it may be safer to aim for somewhat less tight glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 20 publications
5
31
0
Order By: Relevance
“…The average incidence of 6.5 % per year is strikingly similar to that of two recent surveys in childhood diabetes [18,19], and considerably lower than that in two others [20,21] (Table 4), but these rates are notoriously difficult to compare. Egger et al [18] reported a rising incidence of severe hypoglycaemia in a Swiss paediatric diabetic clinic, from 4.4 per 100 patient years from 1981 to 1984 to 7.4 per 100 patient years from 1985 to 1988. This increase corresponded to a change to intensified insulin therapy, and lower mean HbA1 levels.…”
Section: Discussionsupporting
confidence: 75%
“…The average incidence of 6.5 % per year is strikingly similar to that of two recent surveys in childhood diabetes [18,19], and considerably lower than that in two others [20,21] (Table 4), but these rates are notoriously difficult to compare. Egger et al [18] reported a rising incidence of severe hypoglycaemia in a Swiss paediatric diabetic clinic, from 4.4 per 100 patient years from 1981 to 1984 to 7.4 per 100 patient years from 1985 to 1988. This increase corresponded to a change to intensified insulin therapy, and lower mean HbA1 levels.…”
Section: Discussionsupporting
confidence: 75%
“…As can be seen in table 1. patient populations vary dramatically from study to study, with the only common factors among these reports being: (1) children, and (2) 1DDM [1][2][3][4][5][6][7][8][9][10],…”
Section: Problems With the Denominator Of Frequency Calculationsmentioning
confidence: 99%
“…Some investi gators have reported number of episodes per patient-year or per 100 patient-years [2,5,7,9], while others reported number of patients experiencing severe hypoglycaemia per year or per 100 patient-years [1,4,6,10]. l hus, in order to compare the data reported in the studies in ta ble 1, we have calculated both number of patients experi encing severe hypoglycaemia per 100 patient-years and the number of episodes per 100 patient-years whenever the published results permitted such calculations.…”
Section: Problems With the Numerator Of Frequency Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Intensification of insulin therapy may also be associated with an increase in frequency of severe hypoglycaemia in paediatric patients. 5 However, Nordfeldt and Ludvigsson have recently reported that near-normal HbA 1c levels may be achieved without noticeable increase in incidence of severe hypoglycaemia, defined as an episode resulting in unconsciousness. 6 Most published large studies on severe hypoglycaemia in children examine patients on conventional treatment and show an incidence of severe hypoglycaemia (coma and/or convulsion) which varies from 4.8 to 22 episodes per 100 patient-years.…”
Section: Introductionmentioning
confidence: 99%